ANALYSIS OF CROCETANE IN CRUDE OILS AND SEDIMENTS: NOVEL STATIONARY PHASES FOR USE IN GC-MS - Barber C.J.; Bastow T.P.; Grice K.; Alexander R.; Kagi R.I. (My University, 2001)
Cyclodextrin GC stationary phases, well documented for their superior isomeric separation capabilities, have been investigated in the separation of crocetane (2,6,11,15-tetramethylhexadecane) and phytane (2,6,10,14-tetramethylhexadecane). Although crocetane has been attributed to methane oxidizing archaea, its general occurrence in crude oils and sediments is yet to be fully established due to difficulties associated with the GC-MS analysis since crocetane co-elutes with phytane when chromatographed on most liquid phase coated capillary columns. A method is described for the routine GC-MS analysis of crocetane and phytane in crude oils and sediments, using cyclodextrin stationary phases. Numerous derivatised cyclodextrin columns were investigated. A 50 m permethyl-β-cyclodextrin was found to give the best resolution (R=0.8 using hydrogen as the carrier gas and R=0.7 using helium).
Keywords: CROCETANE; PHYTANE; CYCLODEXTRIN STATIONARY PHASES